(untitled) (Research, Society and Development, 2021)
The development and validation of efficient microalgae conservation methods is essential for the establishment and constitution of long-term culture collections, as well as for programming for breeding and possible genetic modification of algae. However, each species of microalgae demonstrates responses considered unpredictable, and thus, making it difficult to standardize universal methods so far. The results presented in this study indicate time as a limiting factor for the conservation of A. obliquus, in the methods of conservation by refrigeration, freezing and freezing with the use of cryoprotectants, such as DMSO, Gli and Poly. Freezing with the use of cryoprotective substances demonstrated satisfactory efficiency in the conservation of microalgae, and thus, surprisingly, in conservation by refrigeration. As already known, conservation by freezing only showed low efficiency, since the cells are broken by the formation of ice crystals in their interior, and thus, making the microalgae conservation unfeasible for a longer period. The study effectively showed the conservation of A. obliquus by refrigeration and freezing with the use of cryoprotective substances mentioned in this work.